IDENTITAS SOSIAL MASYARAKAT GRESIK DALAM TRADISI SANGGRING DI DESA GUMENO (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2024)
The sanggring tradition found in Gumeno Village, Manyar District, Gresik Regency is one of the cultural heritages that is still preserved until now as a form of preserving the ancestral mandate. This can be seen in the implementation of the sanggring tradition every year as well as in the ritual of the implementation of the tradition that does not change. This reseacrh aims to describe the image of social identity according to characteristics of the Gresik people in the sanggring tradition in Gumeno Village. The identity of the Gresik community is seen from the characteristics of the people who are religious, able to preserve culture, and care about social constructs. This research uses qualitative research with type of phenomenological study research. The result of this research show that the sanggring tradition describe three characteristics of the Gresik community, namely, a) the religious character of the Gresik community which is depicted in the process of implementing the sanggring tradition; b) the character of the cultural conservation embedded in the concept of cultural decline and belief; and c) the solidar character thats grow from social equality, personality, as well as community care; and sanggring as a tradition of affirming the identity of the Gresik community. In this study it is concluded that the character of the Gresik community implies that the characretistics of society are part of social identity.